Extensive population admixture on drone congregation areas of the giant honeybee, Apis dorsata (Fabricius, 1793). Issue 24 (2nd December 2014) - Beaurepaire, Alexis L.; Kraus, Bernard F.; Koeniger, Gudrun; Koeniger, Nikolaus; Lim, Herbert; Moritz, Robin F. A.
Abstract The giant honeybee Apis dorsata often forms dense colony aggregations which can include up to 200 often closely related nests in the same location, setting the stage for inbred matings. Yet, like in all other Apis species, A. dorsata queens mate in mid‐air on lek like drone congregation areas (DCAs) where large numbers of males gather in flight. We here report how the drone composition of A. dorsata DCAs facilitates outbreeding, taking into the account both spatial (three DCAs) and temporal (subsequent sampling days) dynamics. We compared the drones' genotypes at ten microsatellite DNA markers with those of the queen genotypes of six drone‐producing colonies located close to the DCAs (Tenom, Sabah, Malaysia). None of 430 sampled drones originated from any of these nearby colonies. Moreover, we estimated that 141 unidentified colonies were contributing to the three DCAs. Most of these colonies were participating multiple times in the different locations and/or during the consecutive days of sampling. The drones sampled in the DCAs could be attributed to six subpopulations. These were all admixed in all DCA samples, increasing the effective population size an order of magnitude and preventing matings between potentially related queens and drones.